Повести: перевод с французского / Франсуаза Саган - Саган Франсуаза (Скорина, 1991)
Экземпляры: ф.10 (1996) / Инвентарный номер: 38684 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: С 13 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-446